TWO PHASE FOR A BETTER FACE!! TWIN BLOCK AND HEADGEAR FOLLOWED BY FIXED THERAPY FOR CLASS II CORRECTION - Nayak, U S Krishna; Shetty, Ashutosh; Soans, Crystal Runa; Bhaskar, Vivek (Journal of Health and Allied Sciences NU, 2015)
Correction of a skeletal sagittal Class II in a growing child can be done either in one single phase of treatment, or in two phases, i.e a first phase of functional appliance to reduce the severity of the skeletal discrepancy, followed by fixed appliance therapy to refine the occlusion. This 2 phase treatment has quite a few advantages such as early correction of the facial profile is seen by the child and parent, which motivates them, as well as, reduces the social handicap produced as a result of the malocclusion. Hence, this case report describes the treatment of a Class II child, with a Twin block appliance followed by fixed orthodontic treatment.
Keywords: Two phase treatment; Twin block; Headgear